Surface electromyographic characteristics of forearm muscles after ulnar and radius fracture inchildren - Qiu, Hailing; Li, Fanling; Zhang, Siqi; Xiao, Sheng; Liu, Haobo; Chen, Shuangxi; Li, Xin; Fang, Ke; Wen, Jie; Li, Tingzhi (Frontiers in Pediatrics, 2023)
Objective: To evaluate the characteristics of forearm muscle activity in children with ulnar and radius fractures during different follow-up periods by surface electromyography. Results: The mean follow-up time was (8.4+2.85) months. Mayo scores were (87.42+13.01) and (97.69±4.50) points at the last follow-up two months after surgery, respectively (p<0.05).In the test of grip strength, 2 months after surgery, the grip strength of the affected side was lower than that of the healthy side (p<0.05), and the maximum and mean values of the superficial flexor of the affected side were lower than those of the healthy side (p<0.05).At the last follow-up, there was no difference in the grip strength between the affected side and the healthy side (p>0.05), and no difference in the maximum RMS, mean RMS and cooperative contraction ratio of the superficial flexor and digital extensor muscles between the affected side and the healthy side (p>0.05). Conclusion: Satisfactory results can be obtained after elastic intramedullary napping in children with ulnar and radius fractures. However, 2 months after surgery, the grip strength of the affected side is small, and the electrical activity of the forearm muscle is low during flexion and extension activities of the wrist joint, which has not returned to normal, suggesting that children orthopaedic clinicians should remind children to conduct timely and effective rehabilitation training after the removal of the cast.